PENGARUH INVESTASI DAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI PROVINSI ACEH - Mila Wardani; T. Dewi Luvitasari; Syafira Handayani Amri (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
The aim of this research isbto determine the influence of Investment and Labor on the economic growth of Aceh Province. The data used is Investment, Labor, and economic growth data for 2011-2020. The data analysis method uses multiple linier regression analysis, t test and F test. The regression equation is Y = 1.291 + 1.260 + 0.556. Form the t test and F test it can be explained that Investment and Labor partially and simultaneously have a significant effect on the economic growth of Aceh Province. From the coefficient of determination test, it is know that Investment and Labor influence economic growth in Aceh Province by 48.8%, while the remaining 51.2% is influence by other variables outside this research model.